Antecedents and Outcomes of Organisational Commitment among Malaysian Engineers - Muthuveloo, Rajendran (2007)
This research explores the major factors that contribute towards Organisational Commitment amongst engineers in Malaysia. It identifies the antecedents of Organisational Commitment and evaluates the impact of Organisational Commitment on Organisational Outcomes. This research project used primary data and the unit of analysis used is individual engineers. The researcher designed a questionnaire to establish that Employee Perception and Personal Characteristics have significant influence on organisational commitment, while Organisational Commitment and Personal Characteristics directly affect Organisational Outcomes. Surveys were distributed to engineers working throughout Malaysia with emphasis on major industrial areas in Selangor, Federal Territory, Johor, Penang, Terengganu, Pahang, Sabah and Sarawak. Data were collected using two methods. Questionnaires were distributed personally to engineers within the Klang Valley vicinity. For the remaining areas, the surveys were mailed to the respondents directly. The findings of the research demonstrate that Employee Perception (via perceived job satisfaction and perceived organisational characteristics) and Attitudinal Characteristic (via race, religion, country of graduation, and academic qualification) enhance organisational commitment through Attitudinal Commitment and Normative Commitment. Organisational Commitment (via Normative Commitment and Continuance Commitment) and Behavioural Characteristic (via age, position, job tenure, and year of service) significantly influence Organisational Outcomes. The study shows that Organisational Commitment is dynamic, relevant, and important for an organisation's survival. However, this study also suggests that high Organisational Commitment can lead to high absenteeism and lower productivity, due to higher work stress. The results also imply that, Organisational Commitment is influenced by engineers' beliefs and values, while Organisational Outcomes are influenced by monetary rewards.